25 Lagu-Lagu Hari Raya Aidilfitri (Selangor: EMI ( Malaysia ) Sdn. Bhd., 2002)
Mengandungi 25 koleksi lagu hari raya
Title from container
Penyanyi: P. Ramlee, Saloma, Sudirman, Rafeah Buang, Fazidah Joned, Sanisah Huri, Uji dan Hail Amir, Sharifah Aini, Black Dog Bone, Ahmad Jais, Junainah M. Amin, Sheila Majid, Rahimah Rahim, Aman Shah, D.J. Dave, Khairil Johari Johar, Rosemaria, Uji Rashid, Anuar & Elina, Cenderawasih, Noorkumalasari
Keywords: Song, Malay; Collections